Answer: Choice C)
![(8)/(9)n - 1(1)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/wz2pcycpxykjaudyxcffulemrp906p2g5m.png)
====================================================
Step-by-step explanation:
We multiply the outer term 4/9 with each term inside
- (4/9) times (2n) = (4*2n)/9 = (8n)/9 = (8/9)n
- (4/9) times (-3) = (4*(-3))/9 = -12/9 = -4/3
The improper fraction 4/3 converts to the mixed number 1 & 1/3
4/3 = (3+1)/3 = 3/3 + 1/3 = 1 + 1/3 = 1 & 1/3
So overall, we can say
![(4)/(9)(2n-3) = (8)/(9)n - 1(1)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/o8c7h5rguhzou2cjt777sdmkzh5ryikfz0.png)
This is equivalent to saying
![(4)/(9)(2n-3) = (8)/(9)n - (4)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/frtila2vnf6jtyyavizqgmor0h066tg0uy.png)